From Panem to the pandemic: an introduction to cultural studies - Butter, Michael 1977- (Narr Francke Attempto, 2023)
"Today, virtually all BA programs in English at German universities place a strong focus on Cultural Studies. However, textbooks that introduce first-year students to the subject are rare, and the few existing ones are too complicated or not comprehensive enough. By contrast, this textbook introduces the key theories and concepts of Cultural Studies systematically and thoroughly. It puts particular emphasis on their application, aiming to enable students to do their own analyses of cultural artefacts and practices. The author draws on many examples, mostly taken from American culture, but in each chapter, he applies the ideas introduced to The Hunger Games franchise and the coronavirus pandemic to show how different theories can lead to very different interpretations of the same phenomenon. Each chapter ends with exercises that allow students to apply what they have learned."
Keywords: Kulturwissenschaften; Amerikanistik; Class; Collective and National Identity; Consumption; Convergence Culture; Coronapandemie; Cultural Studies; Discourse; Ethnicity; Gender; Genre; Hegemony; Ideology; Intersectionality; Kulturwissenschaft; Language; Material Culture; Medium; Memory; Mode; Narrative; Personal; Popular Culture; Production; Race; Regulation; Repräsentation; Sexuality; Space; The Hunger Games; Time; Visual Culture; Lehrbuch